Moderate benefit of escape room game on learning outcome in medicine - Peter Fedorcsak (BMC Medical Education)
Abstract Background Well-designed escape room games engage students with complex problems and challenge clinical and teamwork skills, but their impact on learning has been uncertain. This study aimed to estimate the effect size of escape room game on performance in a broad knowledge test. Methods During clinical rotation in reproductive endocrinology and infertility (REI), medical students participated in a 3-hour small-group class. For 2 semesters, groups had traditional patient visits and case discussions, and for 3 semesters, patient visits and an escape room game including debrief. The game was set up in the outpatient clinic, the puzzles were taken from clinical problems in REI, and challenges included operating an ultrasound scanner on a mannequin. Mid-semester, students completed a test of general knowledge in REI. To estimate the effect of small group class on declarative knowledge, test scores of students who had already had the class (exposed) were compared to scores of those who had not yet had the class (control). Results Students were highly satisfied with gamified teaching. Those who attended the small group class without the escape room game achieved similar scores on knowledge test than control students (Cohen’s d = 0.05, 95%CI -0.58 to 0.68, n = 71). Students who played the escape room game achieved marginally higher score than respective controls (Cohen’s d = 0.22, 95%CI -0.1 to 0.53, n = 182). Conclusions Escape room game may improve learning outcome of a traditional small group class, but the effect of a single game session on declarative knowledge is modest and is unlikely to exceed related instructional methods like simulation.